Accelerated Stack-of-Spirals Free-Breathing Three-Dimensional Ultrashort Echo Time Lung Magnetic Resonance Imaging: A Feasibility Study in Patients With Breast Cancer - Cha, Min Jae; Ahn, Hye Shin; Choi, Hyewon; Park, Hyun Jeong; Benkert, Thomas; Pfeuffer, Josef; Paek, Mun Young (Frontiers in Oncology, 2021)
Purpose: To investigate the clinical feasibility of accelerated free-breathing stack-of-spirals (spiral) three-dimensional (3D) ultrashort echo time (UTE) lung magnetic resonance imaging (MRI) using iterative self‐consistent parallel imaging reconstruction from arbitrary k‐space (SPIRiT) algorithm in patients with breast cancer. Methods: The institutional review board approved this prospective study and patients’ informed consents were obtained. Between June and August 2018, 29 female patients with breast cancer underwent 3-T MRI including accelerated free-breathing spiral 3D UTE (0.98-mm isotropic spatial resolution; echo time, 0.05 msec) of the lungs and thin-section chest computed tomography (CT). Two radiologists evaluated the image quality and pulmonary nodules on MRI were assessed and compared, CT as a reference. Results: The pulmonary vessels and bronchi were visible consistently up to the sub-sub-segmental and sub-segmental branch levels, respectively, on accelerated spiral 3D UTE. The overall image quality was evaluated as good and excellent for 70.7% of accelerated spiral 3D UTE images (reviewer [R]1, 72.4% [21/29]; R2, 69.0% [20/29]) and acceptable for 20.7% (both R1 and R2, 20.7% [6/29]). Five patients on CT revealed 141 pulmonary metastatic nodules (5.3 ± 2.6 mm); the overall nodule detection rate of accelerated spiral 3D UTE was sensitivity of 90.8% (128/141), accuracy of 87.7%, and positive predictive value of 96.2%. In the Bland-Altman plot analysis comparing nodule size between CT and MRI, 132/141 nodules (93.6%) were inside the limits of agreement. Conclusion: Accelerated free-breathing spiral 3D UTE using the SPIRiT algorithm could be a potential alternative to CT for oncology patients.